COMPARATIVE ANALYSIS OF RUSSIAN SHARE MARKET DEVELOPMENT IN 2011–2015 - Irina V. Rozhkova (Plekhanov Russian University of Economics, 2017)
By the end of 2014 economy of the Russian Federation had seriously changed. On the background of economic slump, which started in 2012 and was provoked mainly by structural factors growing geo-political risks and economic sanctions caused restricted access of Russian banks and enterprises to external financing, massed outflow of capital from home economy, changes in situation on home foreign currency market and ruble devaluation. These changes affected negatively the dynamics of Russian share market due to deterioration of securities issuers’ standing and general economic situation that influences investors’ behavior. Comparative analysis of the efficiency of Russian share market development during the last 5 years is an important issue. In this connection the author thinks that researching the share market functioning in Russian economy and directions of its development in complicated current conditions are quite acute. This predetermined the choice of the article topic.